Factors Undermining the Development of Artisanal and Small-Scale Mining in South Africa: A Pathway to the Transformation of the Mining Industry - Khubana, Talifhani (UIN Sunan Gunung Djati Bandung, 2025)
This study seeks to identify the impediments to the development of the ASM industry in South Africa with a focus on prospecting and mining licencing processes. A literature review of the South African mining legislation underpinned the hypothesises formulation. This study used quantitative research methodology. Survey method was used for data collection using items that were self-developed based on study variables. A total of 50 respondents who participated in this study were selected through probability sampling. The empirical results confirmed that despite the fact that ASM provides opportunity for local community members to exercise their rights to participate in and benefit from natural resource management, the regulatory framework for the ASM needed to be revised to holistically address the following challenges: limited access to geotechnical information and technical expertise, lack of institutional support, limited or no access to capital (investment), limited technical ability. The study provides practical recommendations to the ASM industry and policymakers on how to streamline the prospecting and mining licensing processes while simultaneously effectively addressing current challenges. The study fills a knowledge gap on ASM in South Africa because of the dearth of studies on ASM. As a catalyst for equitable economic development, the study also suggests mainstreaming ASM into the economy, taking into consideration the socioeconomic realities and opportunities provided by small deposits.